PROTOTYPE MONITORING SADAPAN NIRA AREN PADA WADAH JERIGEN BERBASIS INTERNET OF THINGS - Dedi, Dedi; Candra, Adi; Nur, Muh. Awal (journal Informatika, Multimedia, dan Informasi, 2024)
This study aims to: 1) To make a prototype of monitoring palm juice leads on internet of things- based jerry cans. 2) To find out the implementation of the prototype monitoring of palm juice leads on jerry cans connected to the blynk.This study uses the prototyping method. The prototyping method is a software development method in the form of a system model and functions as an initial version of the system. This method uses 5 stages, namely the process of collecting data, designing requirements, making designs, making prototypes and evaluating or repairing them. This method will produce a system prototype as an intermediary for developers and users so that they can interact with users and developers.Research results: 1) Prototype monitoring of palm juice leads on internet of things-based jerry can containers designed using fritzing applications and using ultrasonic sensors, Esp8266 with blynk application where the blynk application can be used on android 9 systems. :2) The implementation of the Prototype monitoring tool for palm juice leads on internet of things-based jerry can containers gives good results. This, can be seen from the testing of the ultrasonic sensor system, Esp8266 and blynk application can work well. The sensor detects sap, then Esp8266 will process and the blynk application receives Esp8266 data will display a notification in the form of a message.